(untitled) (Quinto Sol, 2012)
From a social and cultural perspective, this article revises the transition to the sixties and focuses on the way that developmentalism exerted its influence on catholicism, through the new social and cultural practices that it brought, as well as through the new antibourgeois sensibility it also implied.